Peran Masyarakat Dalam Peningkatan Kualitas Produk UMKM Di Desa Wisata Gunungsari - Effendi, Ridwan; Aisyianita, Revi Agustin (Journal of Tourism Sciences, Technology and Industry, 2025)
Gunungsari Tourism Village in Pamijahan District, Bogor Regency, holds significant potential in the tourism sector and creative economy development through Micro, Small, and Medium Enterprises (MSMEs). This study aims to describe community participation in improving the quality of MSME products as a strategy to strengthen the local economy. The research employed a descriptive qualitative method with data collected through observation, in-depth interviews, and documentation. The findings reveal that active community involvement in training, production, and marketing contributes to enhancing product quality and market value. Challenges faced include limited production facilities and low digital promotion capacity. Nevertheless, with institutional support and inclusive community engagement, MSMEs in Gunungsari Village have the potential to become a vital pillar of the sustainable tourism village economy. This study affirms that community participation is a key factor in the development of competitive MSME products.